Innovative Techniques of Teaching English Grammar at Secondary Schools - Rochmawati, Dyah (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
Learning English grammar is always a difficult process to most of the English as Foreign Language (EFL) learners at secondary school level. Innovative ideas, interesting teaching materials, practicing and drilling learners for learning the English grammar should be done through fun and joyful ways. The main aim of this library study was to identify and describe examples of practical grammar instruction methods in an EFL which employed innovative methodologies. The process of the library-based research involves identifying and locating relevant information, analyzing what has been found, and then developing and expressing the ideas. The results revealed that songs and poems, music, games, and tasks can be employed as tools in the classroom. Using innovative methodologies in teaching English grammar in the classroom at the secondary schools has paved a positive way to students to learn the language meaningfully.